Trichodysplasia spinulosa mimicking lichen nitidus in a renal transplant patient. (27th March 2019) - Barone, Hope; Brockman, Ross; Johnson, Luke; Al‐Uzri, Amira; Wright, Mary; Mengden‐Koon, Stephanie; Funk, Tracy
Abstract: Trichodysplasia spinulosa (TS) is a rare cutaneous condition associated with the TSPyV and characterized by skin‐colored, folliculocentric papules with keratin spicule formation. TS is seen almost exclusively in immunosuppressed individuals, often presenting in patients with a history of solid organ transplantation or chemotherapy for a lymphoreticular malignancy. We report a case of widespread TS in a 9‐year‐old girl with a history of renal transplantation complicated by BK viremia, which is also caused by a polyomavirus, BKPyV. The clinical presentation of TS in this case morphologically resembled the more common, harmless skin condition known as "lichen nitidus, " and was more extensive than expected for TS, creating a diagnostic challenge. This case illustrates an important presentation of severe TS of which transplant teams, oncologists, primary care providers, and dermatologists should be aware.